Host and bacterial proteases influence biofilm formation and virulence in a murine model of enterococcal catheter-associated urinary tract infection. (December 2017) - Xu, Wei; Flores-Mireles, Ana; Cusumano, Zachary; Takagi, Enzo; Hultgren, Scott; Caparon, Michael
Abstract Enterococcus faecalis is a leading causative agent of catheter-associated urinary tract infection (CAUTI), the most common hospital-acquired infection. Its ability to grow and form catheter biofilm is dependent upon host fibrinogen (Fg). Examined here are how bacterial and host proteases interact with Fg and contribute to virulence. Analysis of mutants affecting the two major secreted proteases ofE. faecalis OG1RF (GelE, SprE) revealed that while the loss of either had no effect on virulence in a murine CAUTI model or for formation of Fg-dependent biofilm in urine, the loss of both resulted in CAUTI attenuation and defective biofilm formation. GelE−, but not SprE− mutants, lost the ability to degrade Fg in medium, while paradoxically, both could degrade Fg in urine. The finding that SprE was activated independently of GelE in urine by a host trypsin-like protease resolved this paradox. Treatment of catheter-implanted mice with inhibitors of both host-derived and bacterial-derived proteases dramatically reduced catheter-induced inflammation, significantly inhibited dissemination from bladder to kidney and revealed an essential role for a host cysteine protease in promoting pathogenesis. These data show that both bacterial and host proteases contribute to CAUTI, that host proteases promote dissemination and suggest new strategies for therapeutic intervention. Urinary tract infections: targeting enzymes might help Identifying bacterial and host enzymes that support biofilm formation may help prevent urinary tract infections caused by catheters.Enterococcus faecalis bacteria is a leading cause of catheter-associated urinary tract infections, the most common type of hospital-acquired infections. Michael Caparon and colleagues at Washington University School of Medicine in Missouri, USA, studied these infections in mice. They examined the effects of two protein-degrading enzymes, both from the bacterium and one can be activated by urine trypsin-like protease from the animals. Mutations that impaired either one of the enzymes had no effect on the infection, but when both the bacterial enzymes were impaired by mutation the formation of biofilms was significantly reduced. Treating the mice with chemicals that inhibited both bacterial and host enzymes dramatically reduced catheter-induced inflammation and related problems. This suggests drugs targeting these enzymes could be useful in clinical care.